2009
DOI: 10.1161/hypertensionaha.109.129098
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medication Use During Pregnancy and the Risk of Cardiovascular Malformations

Abstract: Abstract-We used data from the National Birth Defects Prevention Study, a population-based, case-control study, to examine whether previously reported associations between antihypertensive medications and cardiovascular malformations could be confirmed and to explore whether new associations might be identified. Cases (nϭ5021) were ascertained through birth defects surveillance systems from 1997 through 2003 in 10 US states. Controls (nϭ4796) were live births without birth defects selected randomly from birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
109
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 44 publications
4
109
1
Order By: Relevance
“…Moreover, mothers exposed to certain antihypertensve drugs are at increased risk of delivering infants with cardiovascular malformations. 37 The current study also showed that maternal epilepsy and mood disorders were associated with an increased risk of congenital heart dis ease in infants. Previous studies have shown that the use of certain anticonvulsants, 38 tran quilizers 39 or hypnotics 40 is associated with an increased risk of congenital heart disease in off spring.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, mothers exposed to certain antihypertensve drugs are at increased risk of delivering infants with cardiovascular malformations. 37 The current study also showed that maternal epilepsy and mood disorders were associated with an increased risk of congenital heart dis ease in infants. Previous studies have shown that the use of certain anticonvulsants, 38 tran quilizers 39 or hypnotics 40 is associated with an increased risk of congenital heart disease in off spring.…”
Section: Discussionsupporting
confidence: 62%
“…5 Although treatment with medication might benefit the mother, it carries potential risks to the fetus from both impaired utero-placental perfusion and foetal exposure to the medications. 6 Study of prescribing pattern is a component of medical audit which seeks monitoring, evaluation and necessary modifications in the prescribing practices of the prescribers to achieve rational and cost effective medical care. Thus, the monitoring of prescription and drug utilization studies can identify the problems and provide feedback to prescribers so as to create awareness about irrational.…”
Section: Introductionmentioning
confidence: 99%
“…4 Similar findings were reported in a smaller Swedish cohort study 5 and a large casecontrol US study. 6 Maternal exposure to angiotensin converting enzyme inhibitors in the first trimester and risk of malformations in offspring: a retrospective cohort study Li et al BMJ 2011;343:d5931 Researchers examined 465,754 mother -infant pairs for the reported link between the use of ACE inhibitors in the first trimester and birth defects. This population based, retrospective cohort study linked automated clinical and pharmacy databases, including comprehensive electronic medical records.…”
mentioning
confidence: 99%